Relação entre geração de valor para o acionista e planejamento tributário - Rocha, Diogo de Souza Salgado (2019)
This research studies the relationship between tax avoidance and shareholder value generation. The essential premise of the study is the colloquial idea that in economizing on tax expenditures there would be an increase in value generation by the firm, and hence to the shareholders. Studies about that subject differ to each others in the metrics used, both to measure shareholder value generation and tax avoidance. In this study, the subject was approached under two propositions to shareholder value: one measured under the perception of the market about the value of the company, adjusting the prices of the shares traded in the open capital market whose metric was the Total Shareholder Return (TRA), the other captures the generation of value through the availability generated in the operational activity measured by the Free Cash Flow to the Equity (FCDA). Tax avoidance was measured by three different metrics: Booktax Difference (BTD), Accruals, and Effective Tax Rate (ETR). The application of each of these metrics was due to its essence, whether accounting or financial, in which for the FCDA was used the ETR and the Accruals, and for the TRA was used the BTD and the Accruals. In order to better identify the relationships between the object of analysis, we also included an analysis by economic sector in which each sample company operates. With the results obtained it was not possible to attribute any significant relationship between the tax avoidance and the generation of value to the shareholder resulting from the market price adjustment (TRA). However, in the generation of value measured by the FCDA, it is possible to attribute an inverse relationship between ETR and FCDA and positive between that and Accruals, which indicates that a reduction in the effective tax rate (ETR) reflects a higher generation of shareholder value, just as a greater treatment of tax matrices (Accruals) reflects an increase in value generation. This observation indicates a positive relationship between tax avoidance and generation of shareholder value within the company's operational scope